Recensions / Book Reviews: JOSEPH S. JOSEPH, Cyprus: Ethnic Conflict and International Politics, from Independence to the Threshold of the European Union - Kaufman, Joyce P. (Études helléniques / Hellenic Studies, 2001)
JOSEPH S. JOSEPH, Cyprus: Ethnic Conflict and International Politics, from Independence to the Threshold of the European Union (London/New York: Macmillan/St. Martin's Press, 1997, third printing 1999), 228 pages. Also available in Greek, Athens, Papazissis publisher, 2000